PENGARUH JUMLAH ZAKAT PRODUKTIF, UMUR PRODUKTIF MUSTAHIK, DAN LAMA USAHA MUSTAHIK TERHADAP PRODUKTIVITAS USAHA MUSTAHIK (Studi pada Baitul Mal Kota Banda Aceh) - Muda, Iskandar; Arfan, Muhammad (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This study is aimed to investigate the influence of productive zakat amount, mustahik productive age, and duration of mustahik enterprises towards the productivity of mustahik enterprises. The number of samples in this study are 38 mustahik who received productive zakat of Baitul Mal Banda Aceh and commited as small traders by using probability sampling technique with random sampling method and using the solvin formula.The data used are the secondary data which directly collected from Baitul Mal Banda Aceh office. To test the hipotesis this study used multiple regression analisys by using SPSS 23.The results of the study show that either simultaniously or partially, the productive zakat amount, mustahik productive age, and the duration of mustahik enterprises effect the productivity of mustahik enterprises.Keywords Productive Zakat, Mustahik Productive Age, Duration of Mustahik Enterprises, and the Productivity of Mustahik Enterprises